1995
DOI: 10.1007/bf00129379
|View full text |Cite
|
Sign up to set email alerts
|

Production of poly(?-hydroxybutyrate-co-?-hydroxyvalerate) from glucose and valerate in Alcaligenes eutrophus

Abstract: Production of poly(~/-hydroxybutyrate-co-//-hydroxyvalerate) [poly (ltB-co-tlV)] in Alcaligenes eutrophus NCIMB 11599 was investigated at various concentrations of valerate. With valerate, higher specific production rate, yield, and IIV content of the copolymer were obtained than those with propionate.By feeding valerate in the copolymer accumulation stage, a product titre as high as 90.4 g/I with ttV content of 20.4 °/6 could be obtained in 50 hi" of fed-batch operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
(1 reference statement)
2
11
0
Order By: Relevance
“…The rate of culture growth and the yield of PHBV decreased considerably at an enhanced pentanol concentration in the mixture, probably due to its toxicity. The toxicity of pentanol and pentanoic acid for bacterial cells was also shown by other authors [5,9,14].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The rate of culture growth and the yield of PHBV decreased considerably at an enhanced pentanol concentration in the mixture, probably due to its toxicity. The toxicity of pentanol and pentanoic acid for bacterial cells was also shown by other authors [5,9,14].…”
Section: Resultssupporting
confidence: 76%
“…Carbohydrates are most often used as the main growth substrates for polymer biosynthesis [11][12][13][14][15][16][17]. In Rus sia, a low cost carbon source is methanol, which is produced in amounts of about 3 million tons per year.…”
mentioning
confidence: 99%
“…On the other hand, valeric acid, as compared to propionic acid, demonstrated the superior convertibility to 3HV units [2]. Previously, P(3HB-co-3HV) with an HV fraction of 20.5 mol% has been obtained in the fed-batch culture of R. eutropha from glucose and valeric acid; however, the detailed feeding protocol of valeric acid was not reported [8]. Rhee et al [14] obtained only 3 mol% 3-HV fraction using glucose as the only carbon source.…”
Section: Resultsmentioning
confidence: 90%
“…With propionic, as a substrate, there is a limitation in obtaining a higher HV fraction [8] which may be due the lower substrate speciWcity of the enzyme 3-ketothiolase for propionyl-CoA [3,5].…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (1996) also reported that 250 g и dm −3 of cells and 130 g и dm −3 of PHB was produced in 70 h of fed-batch culture by controlling methanol concentration within 2 to 3 g и dm −3 by using a microcomputer-aided automatic fedbatch culture system equipped with Teflon-tubing sensor inserted in the fermenter. Further, in fed-batch culture of A. eutrophus, 90 g и dm −3 of poly(␤-hydroxybutyrate-co-␤-hydroxyvalerate) was produced by controlling propionate concentration below 2.0 g и dm −3 (Lee et al, 1995). However, the optimum acetate concentration for cell growth of A. eutrophus was only 1.0 g и dm −3 and the growth was seriously suppressed by either a slight increase or a slight decrease in acetate concentration.…”
Section: Discussionmentioning
confidence: 99%